A compliant dual-axis gripper with integrated position and force sensing. (November 2017) - Chen, Weihai; Qu, Jianliang; Chen, Wenjie; Zhang, Jianbin
Abstract: This paper proposes a new flexure-based dual-axis gripper driven by two piezoelectric actuators (PEAs). For achieving two degree-of-freedom (2-DOF) micromanipulation in terms of grasping and rotating operation, the gripper is designed with an asymmetric structure which can be divided into left and right parts. Each part of the structure includes a two-stage amplification mechanism to accomplish displacement enlargement and motion transmission. Three groups of strain gages are integrated to measure the jaw displacements and the gripping force. To realize decoupling between the grasping and rotating function, the motion-guiding mechanisms of the two parts are elaborately designed with an orthogonal configuration. Analytical models of the gripper are derived using pseudo-rigid-body model (PRBM) method. Finite-element analysis (FEA) simulations are conducted to obtain the optimal geometric parameters and to evaluate the performance of the gripper. A close-loop position/force switching control strategy based on incremental PID algorithm is proposed to compensate the hysteretic nonlinearity of PEAs and guarantee precise and stable operation of the gripper. After that, a prototype gripper is developed and experimental investigations are conducted to verify the effectiveness of the gripper by executing a grasping-rotating-releasing operation of a metal wire. The experimental results indicate that the proposed gripper is capable of delicate and dexterous micromanipulation.